PENATAAN BERKAS ARSIP DINAMIS AKTIF DI BALAI PEMASYARAKATAN KELAS II BUKITTINGGI - , DINDA LUTFIA NUR A ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This final report describes the filing records in Balai Pemasyarakatan Bukittinggi . This final report can be prepared after carrying out the Job Practice . This report uses three methods: the first method of observation, interviews and a literature review methods. These three methods are interrelated with each other to produce the relevant source data or in the preparation of this final report. This report describes the records on Balai Pemasyarakatan Bukittinggi is mail and Research Society records (LITMAS). Mail records stored on Administrative Affairs , while the LITMAS records on a Section BKA and Section BKD . Records storage system in mail using the classification code of the Minister of Law and Human Rights No. 6 of 2012 on Classification Pattern Records . Litmas file storage system using sequential system. Use of a sequential system is to put a new record at the top and bottom sequence to file previous Litmas From observations of the author regarding the arrangement of the records in Balai Pemasyarakatan Bukittinggi is not good enough. This is due to the rediscovery of the records still takes a long time . In addition, existing archival facilities in Bukittinggi Correctional Center has not been used properly.